The Role of the Internet of Things in Healthcare: Future Trends and Challenges. (February 2021) - Aghdam, Zahra Nasiri; Rahmani, Amir Masoud; Hosseinzadeh, Mehdi
Highlights: The Internet of Things will help physicians and hospital staff perform their duties comfortably and intelligently. Health-care is one of the most useful areas for IoT use. A comprehensive overview of the main uses of IoT in health-care has been done. A comprehensive taxonomy of IoT in health-care is presented. The most important challenges the future use of IoT in health-care are highlighted. Abstract: Background and Objective: With the recent advances in the Internet of Things (IoT), the field has become more and more developed in healthcare. The Internet of things will help physicians and hospital staff perform their duties comfortably and intelligently. With the latest advanced technologies, most of the challenges of using IoT have been resolved, and this technology can be a great revolution and has many benefits in the future of digital. Healthcare is one of the most useful areas for IoT use. The most important application of IoT is to monitor and make quick decisions in critical situations. Thanks to this technology-based treatment approach, there is an unprecedented opportunity to better the quality and productivity of treatments and better the patient's well-being and better government funding. Methods: In this paper, we provide a comprehensive overview of the primary uses of IoT in healthcare. We used the Systematic Literature Review (SLR) method to analyze and comparison articles published in this field between 2015 and March 2020. Results: A comprehensive taxonomy is presented based on the contents of the articles under study. In this article, a brief overview of selected articles based on research questions is given and highlights the most critical challenges and case studies for the future use of IoT in healthcare. Conclusions: According to a detailed study of the 89 articles and a glimpse into about 208 articles, challenges and future trends in healthcare have been identified.